Sticking With It: ER-PM Membrane Contact Sites as a Coordinating Nexus for Regulating Lipids and Proteins at the Cell Cortex - Zaman, Mohammad F.; Nenadic, Aleksa; Radojičić, Ana; Rosado, Abel; Beh, Christopher T. (Frontiers in Cell and Developmental Biology, 2020)
Membrane contact sites between the cortical endoplasmic reticulum (ER) and the plasma membrane (PM) provide a direct conduit for small molecule transfer and signaling between the two largest membranes of the cell. Contact is established through ER integral membrane proteins that physically tether the two membranes together. Primary tethers including VAMP-associated proteins (VAPs), Anoctamin/TMEM16/Ist2p homologues, and extended synaptotagmins (E-syts), are largely conserved and are both necessary and sufficient for establishing ER-PM association. In addition, other species-specific ER-PM tether proteins impart unique functional attributes to both membranes at the cell cortex. In yeast, the deletion of seven primary tethers results in phospholipid dysregulation, including defects in phosphoinositide regulation and lipid distribution. In plants, environmental stresses promote dynamic changes ER-PM MCSs and in phosphoinositide distribution. The general mechanism of membrane association is, however, remarkably nonspecific given the diversity of tethering mechanisms, and that chimeric artificial membrane staples can functionally replace endogenous tethers. Nonetheless, ER-PM contact coordinates ER lipid biosynthetic output with the membrane requirements of the PM, including the regulation of phosphoinositide signaling and responses to membrane stresses.